Formation of competitive advantages of Russian transnational corporations in the context of globalization - A. Mozgovoy (Управление, 2019)
The general issues of competitiveness of transnational corporations have been considered. Research of the problem of competitiveness of Russian transnational corporations on the world market and the formation of their competitive advantages for sustainable development in a globalized economy has been сonducted. The author’s interpretation of the concept of “enterprise competitiveness” has been proposed.In a global liberalized economy, transnational corporations have the opportunity to influence geopolitical issues in international trade and employment, as well as dictate their own rules. The constant increase in the level of competitiveness of a small group of transnational corporations has been noted in the article, the format of competition in industry and regional markets is often oligopolistic. Building a true global strategy for the development of transnational corporations and obtaining a competitive advantage by them is impossible without sufficient knowledge of current trends in globalization: globalization of the market, globalization of costs, globalization of competition, globalization of government policies. The methods of obtaining competitive advantages of transnational corporations have been adduced and сharacterized.For Russian transnational corporations, the issue of their competitiveness is very acute in the markets of rapidly turning goods or in the markets of new technologies. Factors, hindering the growth of the competitiveness of Russian corporations: incorrect corporate policies, leading to inefficiency of personnel motivation, corporate culture, inconsistency with international standards, incorrect alignment of the global strategy, lack of reciprocity principles and correct negotiation. This creates a negative image of the company, which affects its position, and subsequently its competitiveness. Competitiveness is one of the most important factors for ensuring the sustainable development of the economy of Russian corporations. The criteria for assessing sustainability, the corporations should meet have been suggested.